2019
DOI: 10.3390/genes10020174
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Genes Responsible for Thermotolerance in Wheat under High Temperature Stress

Abstract: Wheat, a major worldwide staple food crop, is relatively sensitive to a changing environment, including high temperature. The comprehensive mechanism of heat stress response at the molecular level and exploitation of candidate tolerant genes are far from enough. Using transcriptome data, we analyzed the gene expression profiles of wheat under heat stress. A total of 1705 and 17 commonly differential expressed genes (DEGs) were identified in wheat grain and flag leaf, respectively, through transcriptome analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 86 publications
4
15
0
Order By: Relevance
“…In the present study, 23 metabolism-related SDEPs were identified and 21 of them were decreased in maca seedlings following HTS (Additional file 3). This agrees with previous transcriptomic data showing that a specific cluster of genes, which are involved in the metabolism of carbohydrates, amino acids and lipids, are significantly decreased to adapt to the reduced need for primary metabolic products under HTS [15,18]. Furthermore, 11 SDEPs involved in secondary metabolism were identified in the present study.…”
Section: Metabolism Secondary Metabolism and Photosynthesissupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, 23 metabolism-related SDEPs were identified and 21 of them were decreased in maca seedlings following HTS (Additional file 3). This agrees with previous transcriptomic data showing that a specific cluster of genes, which are involved in the metabolism of carbohydrates, amino acids and lipids, are significantly decreased to adapt to the reduced need for primary metabolic products under HTS [15,18]. Furthermore, 11 SDEPs involved in secondary metabolism were identified in the present study.…”
Section: Metabolism Secondary Metabolism and Photosynthesissupporting
confidence: 93%
“…Therefore, the identification of proteins involved in HSRs is crucial to understand the molecular mechanisms of plant response strategies to HTS. To date, although several studies have investigated plant responses to HTS in tomato, grape, rice, and wheat using transcriptomic or proteomic approaches [8,[14][15][16][17][18], the molecular-level mechanisms underlying plant responses to HTS are still not fully understood, at least in herbal plants.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, 27 metabolism-related SDEPs were identified and 25 of them were decreased in maca seedlings following HTS (Additional file 3). This is in line with previous transcriptomic data which showed that a specific cluster of genes, which are involved in the metabolism of carbohydrates, amino acids and lipids, are significantly decreased to adapt to the reduced need of primary metabolic products under HTS [6,11,14]. Furthermore, 13 SDEPs involved in secondary metabolism were identified in the present study.…”
Section: Proteomic Expression Profiles In Maca Seedlings Under Htssupporting
confidence: 93%
“…In response to heat stress, plants accumulate different metabolites such as antioxidants, osmoprotectants, and HSPs that trigger multiple pathways involved in signal transduction, the scavenging of ROS, and maintaining cell membrane stability to improve damage and sustain cell homeostasis [ 49 ]. In the recent past, many studies have been identified and analyzed HSR genes in maize [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%